Penerapan Cerobong Ventilasi pada Desain Rumah Tinggal dengan Fenomena Stack Effect - Edwin Rifanindio (Program Studi Desain Interior Unikom, 2026)
The main problem in small houses located in dense urban areas is the lack of natural sunlight and poor air circulation caused by building density and limited openings, which reduces occupants’ thermal comfort. This study examines the combination of a ventilation chimney and cross ventilation as a passive strategy to improve indoor air quality and natural lighting in a single-story house. The research uses a qualitative-descriptive approach through the study of stack effect theory, natural convection, passive ventilation, and design analysis based on a case study of a residential house located at Jalan Caladi No. 52, Sadang Serang Subdistrict, Coblong District, Bandung City. A 7.70- meter-high ventilation chimney was designed to utilize the temperature difference between indoor and outdoor air in order to generate buoyancy-driven airflow (stack effect). This system is combined with cross ventilation through a corridor inside the building. Natural air movement ranging from 0.2-1.0 m/s can improve occupants’ thermal comfort and help reduce heat accumulation inside the space. The application of the ventilation chimney and cross ventilation in this design is theoretically capable of increasing natural air exchange and accelerating the release of hot air through the vertical shaft. The ventilation chimney also functions as a light well that helps distribute natural lighting into the surrounding spaces. The results of the study indicate that the combination of this passive ventilation strategies has the potential to improve air circulation quality, thermal comfort, and natural lighting in houses located in dense urban environments.